2009
DOI: 10.3171/2009.8.focus09156
|View full text |Cite
|
Sign up to set email alerts
|

Microvascular decompression in patients with isolated maxillary division trigeminal neuralgia, with particular attention to venous pathology

Abstract: Object The authors have the clinical impression that patients with isolated V2, or maxillary division, trigeminal neuralgia (TN) are most often women of a younger age with atypical pain features and a predominance of venous compression as the pathology. The aim of this study was to evaluate a specific subgroup of patients with V2 TN. Methods Among 120 patients who underwent microvascular decompression (M… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
21
0
2

Year Published

2011
2011
2020
2020

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 18 publications
(24 citation statements)
references
References 24 publications
1
21
0
2
Order By: Relevance
“…In microvascular decompression for trigeminal neuralgia, these tributaries not only block access to the nerve but also may be the offending compressing vessel. 13,[26][27][28][29][30][31][32][33][34][35][36][37][38][39][40][41] The transverse pontine veins have been found to be the most frequently compressing veins in trigeminal neuralgia. The veins of the middle cerebellar peduncle, cerebellopontine fissure, and the pontotrigeminal vein have also been reported to be the compressing vein.…”
Section: Superior Petrosal Veinsmentioning
confidence: 99%
See 1 more Smart Citation
“…In microvascular decompression for trigeminal neuralgia, these tributaries not only block access to the nerve but also may be the offending compressing vessel. 13,[26][27][28][29][30][31][32][33][34][35][36][37][38][39][40][41] The transverse pontine veins have been found to be the most frequently compressing veins in trigeminal neuralgia. The veins of the middle cerebellar peduncle, cerebellopontine fissure, and the pontotrigeminal vein have also been reported to be the compressing vein.…”
Section: Superior Petrosal Veinsmentioning
confidence: 99%
“…The veins of the middle cerebellar peduncle, cerebellopontine fissure, and the pontotrigeminal vein have also been reported to be the compressing vein. 13,26,[30][31][32] It is best to try to preserve the superior petrosal veins before electing to sacrifice them to gain surgical access. In the retrosigmoid approach, the semiopaque outer arachnoidal membrane and the arachnoid trabeculae often obscure the superior petrosal veins and their tributaries during the early stages of the exposure.…”
Section: Superior Petrosal Veinsmentioning
confidence: 99%
“…Likewise, the type of vessel compression and the extension of its area of contact along the trigeminal root can also influence symptoms. While arterial compressions, especially at the REZ, are strongly associated with typical-TN, venous compressions usually extend for a larger area and are firmly attached to the trigeminal root (Dandy, 1934); consequently, the latter do not spare any particular group of fibers, and the symptoms are more associated with atypical-TN than with typical-TN (Roski et al, 1982;Sekula et al, 2009). Similar principles apply to the clinical outcome of surgical treatments available for TNP, based on their selective or non-selective harmful effects upon the local groups of trigeminal fibers, sensory and motor.…”
Section: Trigeminal Ganglion and Rootmentioning
confidence: 99%
“…11 While some authors argue that only arterial contact can cause the required pulsatile impact, others hypothesize that this phenomenon can also occur in patients with venous contact due to pulsatile flow that is propagated backward by the heart rate in the absence of intravenous valves. 2,34 Some authors even question the essential role of the pulsatile impact at all. 2,15,24,36 From the clinical perspective, TN-related symptoms do not differ between patients with arterial or venous neurovascular conflicts.…”
Section: 37mentioning
confidence: 99%
“…15,16,34 Currently, it is believed that pulsatile and repetitive mechanical irritations due to direct arterial contact are required and drive the morphological and functional alterations that result in TN: histopathological studies have demonstrated large demyelinated axons, 13,25 loss of axon quantity, 9 and abnormal remyelinization processes within the vulnerable sites of the affected nerve. 24,25 In agreement with these histological findings, neurosurgeons often describe the affected trigeminal nerve as flattened and edematous in situ.…”
Section: 37mentioning
confidence: 99%